Rosmarinic acid ameliorates the complications of monocrotaline-induced right ventricular hypertrophy on the left ventricle: Investigating the signaling pathway of Wnt/β-catenin in the heart - Narges Atefipour; Mahin Dianat; Mohammad Badavi; Maryam Radan; Seyyed Ali Mard (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): Right ventricular hypertrophy (RVH) often results in failure of the right ventricle or even the left ventricle. Rosmarinic acid (RA), a natural polyphenol, is commonly found in Boraginaceae species and some species of ferns and hornworts. This study looked at how RA affects oxidative stress and left ventricular hemodynamic functions as well as RVH in monocrotaline (MCT) induced RVH model rats.Materials and Methods: To cause RVH, MCT (60 mg/kg) was intraperitoneally (IP) injected. Rats were given saline or RA (10, 15, and 30 mg/kg, gavage, over 21 days). In anesthetized rats, the lead II electrocardiogram was recorded. The hemodynamic functions of the isolated heart were measured using the Langendorff apparatus (at constant pressure). Investigations were made into the right ventricular hypertrophy index (RVHI), the activities of superoxide dismutase, catalase, glutathione, and Wnt and β-catenin gene expressions in the left ventricle. H&E staining was used.Results: A significant decline in electrocardiogram parameters and anti-oxidant enzyme activities, an increase in QTc (Q-T corrected) intervals, MDA (Malondialdehyde), RVHI, and Wnt/β-catenin gene expression, and also significant changes in the hemodynamic parameters were demonstrated in the MCT group.  RA improved the above-mentioned factors.Conclusion: According to the findings, RA may act as a cardioprotective agent against cardiovascular complications brought on by RVH due to its capacity to boost the activity of cardiac anti-oxidant enzymes and decrease the expression of genes involved in vascular calcification.